Roles of Bioactive Sphingolipids in Cancer Biology and Therapeutics - Saddoughi, Sahar A. (2008)
In this chapter, roles of bioactive sphingolipids in the regulation of cancer pathogenesis and therapy will be reviewed. Sphingolipids have emerged as bioeffector molecules, which control various aspects of cell growth, proliferation, and anti-cancer therapeutics. Ceramide, the central molecule of sphingolipid metabolism, generally mediates anti-proliferative responses such as inhibition of cell growth, induction of apoptosis, and/or modulation of senescence. On the other hand, sphingosine 1-phosphate (S1P) plays opposing roles, and induces transformation, cancer cell growth, or angiogenesis. A network of metabolic enzymes regulates the generation of ceramide and S1P, and these enzymes serve as transducers of sphingolipid-mediated responses that are coupled to various exogenous or endogenous cellular signals. Consistent with their key roles in the regulation of cancer growth and therapy, attenuation of ceramide generation and/or increased S1P levels are implicated in the development of resistance to drug-induced apoptosis, and escape from cell death. These data strongly suggest that advances in the molecular and biochemical understanding of sphingolipid metabolism and function will lead to the development of novel therapeutic strategies against human cancers, which may also help overcome drug resistance.